In vitro fungitoxic effect of some plant growth regulators on spore germination and germ tube emergence of Alternaria solani - Bhajbhuje MN (International Journal of Life Sciences, 2015)
The inhibitory effect of five plant growth regulators including indol-3-acetic acid; indol-3-butyric acid; naphthalene acetic acid; 2,4-dichlorophenoxy acetic acid; and phenyl acetic acid was evaluated in vitro against the leaf blight pathogen, Alternaria solani. All test chemical inducers at 10-2 to 10-4M conc. significantly reduced spore germination and germ tube growth of the test pathogen. Pathogenic fungus, Alternaria solani had sensitive response against 10-2 conc. of naphthalene acetic acid, reducing spore germination by 84% and germ tube growth by 14% over untreated control. Also, complete inhibition spore germination of test fungal pathogen was confined when all chemical inducers were evaluated at 10-1M conc. Fungal spore germination and germ tube growth increased significantly as the conc. of chemical inducers was decreased. Among the test growth regulators, indol-3-acetic acid had least inhibitory effect against test pathogen of these parameters undertaken. The results of the present study revealed the possibility of usage plant growth regulators in inducing phytoalexin compound in susceptible plant cultivars.